Pain process of patients with cardiac surgery — Semantic annotation of electronic patient record data - Heikkilä Kristiina; Axelin Anna; Peltonen Laura-Maria; Heimonen Juho; Anttila Pauliina; Viljanen Timo; Salakoski Tapio; Salanterä Sanna (Blackwell Scientific, 2022)
Aims and objectives: To describe and compare the pain process of the patients’ with cardiac surgery through nurses’ and physicians’ documentations in the electronic patient records.
Background: Postoperative pain assessment and management should be documented regularly, to ensure optimal pain care process for patients. Despite availability of evidence‐based guidelines, pain assessment and documentation remain inadequate.
Design: A retrospective patients’ record review.
Methods: The original data consisted of the electronic patient records of 26,922 patients with a diagnosed heart disease. A total of 1,818 care episodes of patients with cardiac surgery were selected from the data. We used random sampling to obtain 280 care episodes for annotation. These 280 care episodes contained 2,156 physician reports and 1,327 days of nursing notes. We developed an annotation manual and schema, and then, we manually conducted semantic annotation on care episodes, using the Brat annotation tool. We analysed the annotation units using thematic analysis. Consolidated criteria for reporting qualitative research guideline was followed in reporting where appropriate in this study design.
Results: We discovered expressions of six different aspects of pain process: (a) cause, (b) situation, (c) features, (d) consequences, (e) actions and (f) outcomes. We determined that five of the aspects existed chronologically. However, the features of pain were simultaneously existing. They indicated the location, quality, intensity, and temporality of the pain and they were present in every phase of the patient’s pain process. Cardiac and postoperative pain documentations differed from each other in used expressions and in the quantity and quality of descriptions.
Conclusion: We could construct a comprehensive pain process of the patients with cardiac surgery from several electronic patient records. The challenge remains how to support systematic documentation in each patient.
Relevance to clinical practice: The study provides knowledge and guidance of pain process aspects that can be used to achieve an effective pain assessment and more comprehensive documentation.